(untitled) (International Conference on Computers in Education, 2011)
The purpose of present study is to explore peoples’ online medical information commitments (MIC) and to compare peoples’ online MIC between different groups. A Medical Information Commitment Survey (MICS) was employed to investigate peoples’ evaluative standards of assessing online medical information and their searching strategies used on Internet. Two groups, including 247 samples from the group of people in hospital and 293 samples from the group of people in general public, were surveyed. The results showed that the MICS was a sufficiently reliable tool to assess peoples’ MIC. It was also found that for seeking more credible online medical information, people would tend to employ both basic and sophisticated evaluative standards (i.e. mixed standards) for judging online medical information, and to utilize “elaboration,” the advanced searching strategy, as well. Especially for people in hospital, they showed higher tendencies to use mixed standards and “elaboration” searching strategy than people in general public.